Impact of Event Indonesia Fashion Week to Wardah's Brand - Sa'diyah El Adawiyah; Alfa Taufan Latif; Anwar Ilmar Ramadhan (BASKARA : Journal of Business and Entrepreneurship, 2020)
Indonesia Fashion Week Event (IFW) is a movement in the fashion sector initiated by the Indonesian Fashion Designers Association (APPMI). This movement aims to make Indonesia as one of the world's fashion centres. This event held regularly every year since 2010. This event is Wardah's event as one of the famous cosmetic brands to increase awareness. This study aims to measure how much influence the Indonesia Fashion Week (IFW) Event on Wardah's Image is in the Jabodetabek Hijabers Community. The theory used in this study is the theory of public relations, the theory of events and the theory of image. This study uses a quantitative approach to analytical methods. This method is to examine the influence between Variables (X) and Variables (Y). Data collection techniques using questionnaires distributed in Hijabers Community using accidental sampling techniques. From the results of research and discussion, it can see that the dimensions of Perishability at the Indonesia Fashion Week event have the lowest average value among the four other variables 73.6%. Which means that the Indonesia Fashion Week event schedule does not have an event schedule must adjust to the target visitors and participant following the theme carried. Besides, the results of the second study that Wardah's Image is in the "Good" category. It proves from the results of the comparison of the results obtained with the achievement value of 82.3%. The results of the third study, the Indonesia Fashion Week 2018 event was able to increase Wardah's image in the Jabodetabek Hijabers Community. Based on the calculation of the Determinant Coefficient, the value of the Indonesia Fashion Week Event is 0.3169 or 31.69%. The Indonesia Fashion Week Event influences Wardah's image at 31.69%, and other variables determine the remaining 68.31%.